2007
DOI: 10.1038/nnano.2007.389
|View full text |Cite
|
Sign up to set email alerts
|

Improved broadband and quasi-omnidirectional anti-reflection properties with biomimetic silicon nanostructures

Abstract: Nature routinely produces nanostructured surfaces with useful properties, such as the self-cleaning lotus leaf, the colour of the butterfly wing, the photoreceptor in brittlestar and the anti-reflection observed in the moth eye. Scientists and engineers have been able to mimic some of these natural structures in the laboratory and in real-world applications. Here, we report a simple aperiodic array of silicon nanotips on a 6-inch wafer with a sub-wavelength structure that can suppress the reflection of light a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
482
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,004 publications
(501 citation statements)
references
References 37 publications
18
482
1
Order By: Relevance
“…By optimizing the variance of the distribution and the shape of the pedestals, almost perfect antireflection surfaces can be engineered for a broadband range of wavelengths and a wide range of viewing angles. Such antireflective surfaces could be adapted to improve the light collection in solar cells or for an efficient light extraction of the substrate modes in light-emitting diodes or even enhancing the performance of the optical, optoelectronic and electro-optical devices, such as glasses, mirrors, lens, photodetectors, surface-emitting lasers, displays and optical sensing or imaging 20,21,[30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By optimizing the variance of the distribution and the shape of the pedestals, almost perfect antireflection surfaces can be engineered for a broadband range of wavelengths and a wide range of viewing angles. Such antireflective surfaces could be adapted to improve the light collection in solar cells or for an efficient light extraction of the substrate modes in light-emitting diodes or even enhancing the performance of the optical, optoelectronic and electro-optical devices, such as glasses, mirrors, lens, photodetectors, surface-emitting lasers, displays and optical sensing or imaging 20,21,[30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…A master mould of these structures can be produced by advanced etching techniques 30 . Moulds replicated from such a master can be used for thermal nanoimprint 33 or hot embossing 34 to replicate glasswing structures on large scales.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient anti-reflection coatings (AR) have been intensively studied with many different approaches having been explored for this purpose [1][2][3] , such as multi-layered thinfilms 4,5 , graded index matching via surface texturing with micro-and nano-structures [6][7][8][9][10][11] , plasmonic metasurfaces [12][13][14] and more recently, metasurfaces [15][16][17][18][19][20][21] based on ordered arrays of sub-micrometric dielectric antennas (dielectric Mie resonators [22][23][24][25][26][27][28] ). Depending on the application of the AR different aspects (lowest value of the total reflectance, broad spectral range, broad acceptance angle, transparency or light trapping) determine the optimal features and fabrication method.…”
Section: Introductionmentioning
confidence: 99%
“…Though photovoltaic sun tracking system is effective to solve the problem induced by the changed θ, it is costly and difficult to work precisely for more than 20–25 years of module lifetime 1. In recent years, there are lots of reports demonstrating that Si nanostructures possess outstanding broadband and omnidirectional antireflection ability, which are promising to be adopted in solar cells to form omnidirectional solar cells for enhancing electric energy output over broad θ 2, 3, 4, 5, 6, 7, 8, 9. For example, Spinelli et al2 have reported that Si nanocylinder arrays can effectively suppress reflection over the wide θ of 0°–60°.…”
Section: Introductionmentioning
confidence: 99%